Engaging Ethnic Restaurants to Improve Community Nutrition Environments: A Qualitative Study with Hispanic Caribbean Restaurants in New York City. Issue 3 (3rd May 2020) - Fuster, Melissa; Guerrero, Kevin; Elbel, Brian; Ray, Krishnendu; Huang, Terry T-K
ABSTRACT: This study used interviews with New York City Hispanic Caribbean (HC) restaurant owners, managers, and cooks/chefs (n=19) to examine perceptions concerning the healthfulness of the HC diet and diet-related disparities in the HC community, and document factors potentially influencing their engagement in community nutrition interventions. The interviews revealed high awareness of diet-related issues. Respondents had mixed notions concerning their role in improving community food environments, noting important barriers for collaboration to consider in future interventions. The study underscores the important role of ethnic restaurants, providing information to facilitate engagement with this largely untapped sector in immigrant/ethnic communities in the US.